Hubungan Antara Keaktifan Mengikuti Kegiatan Pimpinan Komisariat (PK) IPNU/IPPNU Dengan Sikap Sosial Keagamaan Siswa MTs Sunan Gunung Jati Katemas Kudu Jombang - Rosyidah, Uun Nur; Rohmah, Hidayatur; Chotimah, Chusnul (Universitas KH. A. Wahab Hasbullah, 2022)
This research was conducted at MTs Sunan Gunung Jati Katemas which discussed the relation between activeness following the activities of Pimpinan Komisarian (PK) ) IPNU/IPPNU with Religious Social Attitudes at MTs Sunan Gunung Jati Katemas Kudu Jombang Academic Year 2019/2020. This research aims to answer the following problemsIs there a relation between active participation in activities of Pimpinan Komisariat (PK) IPNU / IPPNU with the religious social attitude of students at MTs Sunan Gunung Jati.This research used a type of field research. The research population was 30 respondents. Research data was collected then analyzed using statistical analysis techniques. Testing the research hypothesis using Product Moment correlation analysis. This research showed that there is a relation between the activeness of participating in the activities of Pimpinan Komisariat (PK) IPNU / IPPNU and the religious social attitudes of students at MTs Sunan Gunung Jati Katemas. This is based on the data was obtained, where rxy = 0.720 is greater than r table with a significance level of 5%, that is = 0.361, so rcount> rtabel, then the hypothesis is accepted, that is, there is a significant relationship between variable X (activeness following the activities of Pimpinan Komisariat (PK) IPNU / IPPNU) with variable Y (religious social attitude of students at MTs Sunan Gunung Jati Katemas).